FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR GANDUM INDONESIA - Yogi Pradeksa; Dwidjono Hadi Darwanto; Masyhuri Masyhuri (Agro Ekonomi, 2014)
The purpose of this research are to determine the factors that influence the Indonesian wheat imports and the trend of Indonesian wheat imports. The method used in this research was descriptive analysis method using time series data from the years 1992 to 2011. The variables used are national income (GNP), population, international wheat prices, domestic rice prices, exchange rates, and the use of wheat flour by industry. The trend of import volume of wheat showed that there will be additional of import wheat volume around of 11.793 ton per year. Determinant factors which significantly affecting import volume of wheat are national income (GNP), population, international wheat prices and exchange rates, while the domestic rice prices and the use of wheat flour by industry had no significant effect on the volume of imports.